Photonic Sensing: Stretchable Optomechanical Fiber Sensors for Pressure Determination in Compressive Medical Textiles (Adv. Healthcare Mater. 15/2018). Issue 15 (8th August 2018) - Sandt, Joseph D.; Moudio, Marie; Clark, J. Kenji; Hardin, James; Argenti, Christian; Carty, Matthew; Lewis, Jennifer A.; Kolle, Mathias
Abstract : Color‐tunable photonic fibers, which reversibly change their vivid reflective coloration upon elongation, derive their functionality from the use of highly stretchable elastomers in familiar photonic structures. In article1800293, Mathias Kolle and co‐workers demonstrate how these devices can substantially improve the efficiency and efficacy of compression therapy, by acting as easily‐interpreted indicators of applied pressure when integrated into elastic bandages.